CTNI-16. TROTABRESIB (CC-90010, BMS-986378), A REVERSIBLE, POTENT ORAL BROMODOMAIN AND EXTRATERMINAL INHIBITOR (BETi) IN PATIENTS WITH HIGH-GRADE GLIOMAS: A PHASE 1 OPEN-LABEL 'WINDOW OF OPPORTUNITY' STUDY. (12th November 2021) - Vogelbaum, Michael; Sepulveda, Juan Manuel; Reardon, David; Hanna, Bishoy; Filvaroff, Ellen; Aronchik, Ida; Amoroso, Barbara; Zuraek, Marlene; Sanchez-Perez, Tania; Mendez, Cristina; Nikolova, Zariana; Moreno, Victor
Abstract: Trotabresib is a potent, reversible oral BETi with antitumor activity in patients with advanced malignancies (Moreno et al. ESMO 2020. Abstract 5270). The CC-90010-GBM-001 study (NCT04047303) enrolled patients with progressive or recurrent astrocytoma or recurrent glioblastoma scheduled for salvage resection. Patients were treated with trotabresib 30 mg daily for 4 days before surgery, then trotabresib 45 mg daily 4 days on/24 days off after recovery. Primary objectives were trotabresib tumor tissue concentration and plasma pharmacokinetics (PK). Secondary and exploratory objectives included safety, antitumor activity, cerebrospinal fluid concentration, and pharmacodynamics (PD). Twenty patients were enrolled; blood PK, blood PD, and tumor PD data were available for 14, 12, and 11 patients, respectively. Geometric mean peak trotabresib plasma concentration on day 4 was 1.92 μM; median time to peak concentration was 1.5 hours. At the time of resection, geometric mean trotabresib concentrations in plasma and brain tumor tissue were 1.01 and 0.68 μM, respectively. Blood CCR1 mRNA was reduced ≥ 50% from baseline after dose 4. Blood HEXIM1 mRNA increased at 72–96 hours following first dose, and at the time of surgery the percentage increase was related to plasma trotabresib concentration. Tumor HEXIM1 RNA increased in 10 of 11 patients. Eighteen patients (90%) had ≥ 1 treatment-related adverse event (TRAE). Nine patients (45%) had grade 3/4 TRAEs, most frequently thrombocytopenia (5 patients [25%]). Only 1 patient had serious TRAEs (hemiparesis and lethargy). Two patients died of intracranial hemorrhage unrelated to study drug. Of 16 patients evaluable for antitumor response, 7 had stable disease per RANO criteria, with 3 ongoing beyond data cutoff at cycles 4–11. Median progression-free survival was 1.9 months (95% CI, 1.4–3.3). Overall, trotabresib showed good tumor tissue penetration, with PD signals of response, and was well tolerated. A study of trotabresib + temozolomide in first-line glioblastoma is ongoing (NCT04324840).